Kajian Tingkat Pengetahuan Dagusibu Antibiotik Pada Siswa Farmasi SMK YPKK 1 Sleman - Anggeraini , Via Gusti; Sugiyono, Sugiyono; Larasati, Niken (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA, 2024)
Background: Antibiotics are effective in stopping the growth of bacteria and eliminating infections. However, improper use of antibiotics can lead to bacterial resistance, highlighting the importance of proper management. This management includes the appropriate ways to obtain, use, store, and dispose of antibiotics, commonly referred to as DAGUSIBU. Pharmacy students, who will later undergo internships in pharmacies and hospitals, need comprehensive knowledge about DAGUSIBU for antibiotics to effectively educate the public. Objective: This study aims to examine the relationship between specific characteristics age, gender, and learning level and the level of knowledge regarding DAGUSIBU for antibiotics among pharmacy students at SMK YPKK 1 Sleman. Method: This research employed a descriptive observational design with a cross-sectional approach. Data collection was conducted using a printed questionnaire. The study involved 41 students selected through total sampling. Data analysis was performed using univariate and bivariate methods. Univariate analysis was used to describe students' characteristics and their level of knowledge, while bivariate analysis utilized the Chi-square test to determine relationships between the students' characteristics and their knowledge levels. Results: The results showed that the majority of pharmacy students at SMK YPKK 1 Sleman were over 17 years old (63.4%), predominantly female (73.2%), and most commonly at the lowest learning level, grade X (34.1%). In terms of knowledge about DAGUSIBU for antibiotics, 29.2% of students had good knowledge, while 70.8% had poor knowledge. The Chi-square test revealed significant relationships between age (p-value: 0.000) and learning level (p-value: 0.001) with knowledge levels, while no significant relationship was found for gender (p-value: 0.524). Conclusion: There is a significant relationship between students' age and learning level and their knowledge of DAGUSIBU for antibiotics. However, gender does not show a significant correlation with their level of knowledge regarding DAGUSIBU for antibiotics.